2022
DOI: 10.31273/978-1-911675-05-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 pandemic on Hospices (ICoH): Senior Management Cohort and Grey Evidence Report

Abstract: This report describes the diversity of experiences of people with life-limiting illnesses who were supported by hospices in the West Midlands during the pandemic. It is one of four cohort reports – the others focus on patients, carers, and frontline hospice staff respectively – that form the evidence base for a Policy Report into the impact of Covid-19 on hospices. In these reports we address the nine key themes that were identified as potentially important in our previous collaborative knowledge synthesis (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The impact of COIVD-19 on Hospices (ICOH) study (19) is the only other study to have used in-depth interviews with carers in a hospice context. They similarly found that despite many of the best efforts of frontline healthcare professionals, hospice care was compromised and fell below the "gold standard" expected (19).…”
Section: Discussion and Recommendations For Policy Practice And Publi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of COIVD-19 on Hospices (ICOH) study (19) is the only other study to have used in-depth interviews with carers in a hospice context. They similarly found that despite many of the best efforts of frontline healthcare professionals, hospice care was compromised and fell below the "gold standard" expected (19).…”
Section: Discussion and Recommendations For Policy Practice And Publi...mentioning
confidence: 99%
“…The impact of COIVD-19 on Hospices (ICOH) study (19) is the only other study to have used in-depth interviews with carers in a hospice context. They similarly found that despite many of the best efforts of frontline healthcare professionals, hospice care was compromised and fell below the "gold standard" expected (19). The study also included patients and offers further support for our findings that all those who came in contact with the visiting restrictions (patients, cares, and managers) experienced emotional distress.…”
Section: Discussion and Recommendations For Policy Practice And Publi...mentioning
confidence: 99%